COMBINED EFFECT OF TOPICAL APPLICATION OF VIRGIN COCONUT OIL (VCO) AND BLACK CUMIN OIL (NIGELLA SATIVA) ON THE UPREGULATION OF VEGF GENE EXPRESSION AND WOUND HEALING IN DIABETIC ULCERATED RATS. - ARMAN, ELIZA; A., ALMAHDY; DAFRIANI, PUTRI; ALMASDY, DEDY (International Journal of Applied Pharmaceutics, 2024)
Objective: Traditional therapies are increasingly explored as alternative methods for the management of diabetic ulcer. VCO and black cumin oil has attracted attention for its potential therapeutic benefits in promoting skin wound healing. Methods: The rats were induced with one dose diabetes mellitus through the of intraperitoneal injection of streptozotocin 55 mg/kg body weight. Furthermore, fasting blood glucose (FBG) levels were monitored weekly for assessment. The wound was created using a 10-mm diameter punch biopsy. An experimental methodology was used, comprising the division of 30 rats into six groups, namely control, VCO, black cumin oil, and combinations of VCO and black cumin oil labeled as C1, C2, and C3. The formulated treatments were topically applied to wound for 7 and 14 d. At the end of the treatment, the samples were sacrificed and wound was excised, followed by molecular biological analysis and histopathological examination. Results: On day 7, VEGF gene expression showed the highest increase in the C3 group, with an average of 1.85±0.10. Meanwhile, the highest increase on day 14 was observed in the C3 group, with an average of 1.69±0.11. C3 group treated wounds healed much faster, as indicated by a decreased time of complete epithelization and higher levels of various skin components. Conclusion: The combination of VCO and black cumin oil could be used as an agent to accelerate wound healing in diabetic conditions, as indicated by the increased expression of VEGF gene.